Peran Kepala Sekolah Dalam Meningkatkan Kualitas Sekolah Melalui Program Unggulan SDN 008 Muara Wahau - Ahmad Miftahudin; Heri Hermanto; Muh Fauzan (PT. Pustaka Andil Lestari, 2024)
State Elementary School 008 Muara Wahau has a flagship program that is a foreign language learning program (English and Arabic) with the hope of achieving predetermined goals. This study aims to determine the role of the principal in improving school quality through excellent programs, and to determine the principal's strategy in improving school quality through excellent programs at SDN 008 Muara Wahau. The qualitative method was applied in this study. The descriptive technique was employed in the investigation. Data collecting methods include observation and interviews. The findings of this study indicate that (1) the principal's role in improving school quality through excellent programs is that of an educator, manager, administrator, and supervisor; and (2) the principal's strategy for improving school quality through excellent programs is that of planning, organizing, implementing, and supervising.